2012
DOI: 10.2131/jts.37.297
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumor promoting effect of etofenprox in rats and its possible mechanism of action

Abstract: -To investigate the liver tumor-promoting effects of etofenprox (ETF), a pyrethroid-like insecticide, 6 week-old male F344 rats were given an intraperitoneal injection of N-diethylnitrosamine (DEN). After 2 weeks from the DEN treatment, 12 rats per group received a powdered diet containing 0, 0.25, 0.50, or 1.0% ETF for 8 weeks. At the time of 2nd week of ETF administration, all animals were subjected to two-thirds partial hepatectomy (PH). One rat per group except for the 0.25% ETF group died due to surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Hojo et al found etofenprox had a stimulating effect on liver tumor in rats and increased reactive oxygen species production in microsomes isolated from the livers of etofenprox treated rats. Besides the thiobarbituric acid-reactive substances levels and 8-OHdG content also significantly increased in all of the etofenprox treated groups (22).…”
Section: Discussionmentioning
confidence: 85%
“…Hojo et al found etofenprox had a stimulating effect on liver tumor in rats and increased reactive oxygen species production in microsomes isolated from the livers of etofenprox treated rats. Besides the thiobarbituric acid-reactive substances levels and 8-OHdG content also significantly increased in all of the etofenprox treated groups (22).…”
Section: Discussionmentioning
confidence: 85%
“…ETF induces liver tumor-promoting effects via increased cellular proliferation. (4). Hayashi et al (5) reported that contamination of rice-based chow with etofenprox, diethyl phthalate, and alkylphenols significantly impaired first delivery and sperm counts in mice.…”
Section: Introductionmentioning
confidence: 99%